Influence of ZnO Nanoparticles on Candida albicans of Human Male Pleural Fluid - Katafa, Anfal J.; Hamid, Mazin K. (Iraqi Journal of Science, 2020)
The utilization of metal oxide nanoparticles, especially zinc oxide, is of a great importance in the medical field because of its physical and chemical properties as well as its antimicrobial potential effects. In our study, the ZnO nanoparticles were synthesized by the precipitation method where pH=14. ZnO nanoparticles were characterized by ultraviolet–visible spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM) and atomic force microscope (AFM). Antifungal activity of the ZnO was tested against candida albicans. The results showed that C. albicans (15 samples) became resistant to the fungal activity after testing its sensitivity to several types of fungal antibiotics. UV-vis spectroscopy, XRD, TEM and AFM showed that this precipitation synthetic method can produce a good quality of ZnO nanoparticles with sizes in the range of nanometer scale. In ZnO NPs (calcined), the inhibition zone diameter of C. albicans was 11 mm at a ZnO NPs concentration of 800 mg/ml, while no inhibition zones were formed at the other concentrations (0.25, 0.5, 1, 2, 10, 50 and 500 mg/ml). Using ZnO NPs (not calcined), the inhibition zone diameter of C. albicans was 24 mm at a concentration of 800 mg/ml, while no inhibition zones were observed at the other concentrations (0.25, 0.5, 1, 2, 10, 50 and 500 mg/ml). In addition, a toxicity test was performed on mice and proved that ZnO NPs are effective against C. albicans with a toxic effect on liver and spleen cells in rats. The aim of this research was to characterize the in vitro activity of ZnO nanoparticles synthesized by the precipitation method against C. albicans of human male pleural fluid using the well diffusion method as well as their toxic effects on both liver and spleen cells in mice.